Carbon footprint of drinking water over treatment plant life span (2025–2075) is probably dominated by construction phase - Bas Hofs (Cleaner Environmental Systems, 2022)
Drinking water companies must limit their effects on climate change. Therefore, in this study, we conducted a hybrid life cycle assessment (LCA) for a new drinking water treatment plant (DWTP) to be built in 2025 and expected to be operational until 2075. We focused on obtaining a nearly complete carbon footprint (CF), including both construction (activities and materials) and operation phases. We compared three DWTP concepts: (i) conventional treatment followed by granular activated carbon (GAC) and ultrafiltration; (ii) conventional treatment followed by reverse osmosis; and (iii) capillary nanofiltration followed by GAC. As the DWTP is to be built in The Netherlands, we considered the current plans of the European Union for reducing CFs using two future scenarios (reductions of 80% and 100% in 2050). We found that the CF of the construction over the lifetime of the DWTP accounts for 20–70% of the total (excluding beneficial effects), depending mainly on the electricity used (Dutch mix, solar, or wind) and the future scenario. This means that the construction phase should be investigated in detail to obtain a complete and accurate estimate of the total CF of drinking water production for new DWTPs.